Physician Perceptions of Children’s Coping with Asthma are Associated with Children’s Psychosocial and Disease Functioning - Rodríguez, Erin M. (Fam Syst Health, 2017)
INTRODUCTION: Low-income, ethnic minority children disproportionately face poor asthma control, and poorly controlled asthma is related to psychosocial difficulties. This study assessed physician reports of coping in child patients, and examined associations between physician reports of child coping and parent and child reports of children’s coping, psychosocial and asthma outcomes (asthma-related stress, emotional and behavioral problems, asthma control, and school missed due to asthma). METHODS: Physicians reported on coping in their patients (N=67) ages 5–17 with asthma. Parents reported on child coping, asthma-related stress, emotional and behavioral problems, asthma control, and school missed due to asthma. Children ages 9–17 provided self-reports. RESULTS: Physicians’ reports of primary control coping (e.g., problem solving) and secondary control coping (e.g., cognitive restructuring) were not associated with parent ratings of corresponding coping strategies, but physician reports of disengagement coping (e.g., avoidance) were correlated with parent reports of disengagement and secondary control coping. Physician perceptions of higher child primary control, and lower disengagement, were correlated with less parent-reported stress, better asthma control, and for primary control, fewer partial days of school missed. Physician reports were not correlated with child reports of coping, but physician reports of disengagement were correlated with child-reported conduct problems. DISCUSSION: Findings suggest that physician reports of child coping provide independent information from parent and child reports of coping, and could be leveraged to identify and intervene with patients who are at elevated risk for poor outcomes.